Tuberculosis: a neglected disease - Janete Aparecida Machado; Mariana S. Adam; Marcelo Carneiro; Aline Scheibler; Camila Haas; Lia Gonçalves Possuelo; Eloete B. Stahlecker (Universidade de Santa Cruz do Sul, 2011)
.